Whistle-blowers - morally courageous actors in health care? - Wiisak Johanna; Suhonen Riitta; Leino-Kilpi Helena (SAGE PUBLICATIONS LTD, 2022)
Background:
Moral courage means courage to act according to individual's own ethical values and principles despite the risk of negative consequences for them. Research about the moral courage of whistle-blowers in health care is scarce, although whistleblowing involves a significant risk for the whistle-blower.
Objective:
To analyse the moral courage of potential whistle-blowers and its association with their background variables in health care.
Research design:
Was a descriptive-correlational study using a questionnaire, containing Nurses Moral Courage Scale((C)), a video vignette of the wrongdoing situation with an open question about the vignette, and several background variables. Data were analysed statistically and inductive content analysis was used for the narratives.
Participants and research context:
Nurses as healthcare professionals (including registered nurses, public health nurses, midwives, and nurse paramedics) were recruited from the membership register of the Nurses' Association via email in 2019. A total of 454 nurses responded. The research context was simulated using a vignette.
Ethical considerations:
Good scientific inquiry guidelines were followed. Permission to use the Nurses' Moral Courage Scale((C)) was obtained from the copyright holder. The ethical approval and permission to conduct the study were obtained from the participating university and the Nurses' Association.
Findings:
The mean value of potential whistle-blowers' moral courage on a Visual Analogue Scale (0-10) was 8.55 and the mean score was 4.34 on a 5-point Likert scale. Potential whistle-blowers' moral courage was associated with their socio-demographics, education, work, personality and social responsibility related background variables.
Discussion and conclusion:
In health care, potential whistle-blowers seem to be quite morally courageous actors. The results offer opportunities for developing interventions, practices and education to support and encourage healthcare professionals in their whistleblowing. Research is needed for developing a theoretical construction to eventually increase whistleblowing and decrease and prevent wrongdoing.